PENGARUH PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Ernawati, Dewi; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
A company through its financial manager should beable to run its function in managing financeproperly and as efficient as possible. The standard which is used to assess the success of a financialmanagerin managing the finance of the company is from the firm value. The firm value can reflect thecondition of the company. There are many factors which can determine the firm value. This research isconducted to test the influence of profitability, leverage, and firm size to the firm value on themanufacturing companies which are engaged in the field of consumer goods industry which are listedin Indonesia Stock Exchange.The samples are 22 manufacturing companies which are engaged in thefield of consumer goods industries which are listed in Indonesia Stock Exchange. The sample collectiontechnique has been carried out by using purposive sampling technique. The data is the secondary data.The data analysis has been carried out by using classic assumption test, the multiple regressionsanalysis and the hypothesis test which is done by using t test and F test with the level of significance5% are used as the data analysis technique.The result of the analysis shows that profitability haspositive influence to the firm value, with the significance value 0.000 is smaller than Î± = 0.05 and theregressions coefficient is 0,074. The leverage has negative influence to the firm value, with thesignificance value 0.097 is bigger than Î± = 0.05 and the regressions coefficient is -1.641. The firm sizehas positive influence to the firm value with the significance value 0.000 is smaller than Î± = 0.05 andthe regressions coefficient is 0.353.Keywords: Profitability, Leverage, Firm Size and Firm Value.